Numerical Analysis of Hydrodynamic and Channel Discharge Impacts of Planned Coastal Reclamation in Eastern Surabaya - Ishak, Muhammad; Suntoyo; Pratikto , Widi Agoes (Maritime Park: Journal of Maritime Technology and Society, 2025)
Reclamation is a widely adopted strategy to address land scarcity by converting coastal waters into new land. This approach has been implemented in many major cities worldwide to support economic growth and infrastructure expansion, including in Surabaya. As the core of the Gerbangkertosusila National Strategic Area, Surabaya is actively pursuing coastal development, one of which is the planned integrated reclamation project, Surabaya Waterfront Land (SWL), in the Pamurbaya region. Previous studies have shown that reclamation can significantly alter hydrodynamic processes, including river discharge in estuarine channels. This study investigates changes in hydrodynamic patterns and primary channel discharges following reclamation, using numerical simulations with Delft3D. Model performance was validated with a Root Mean Square Error (RMSE) of 0.4. The results indicate that reclamation increases current velocities in the southern sector to ≥1.5 m/s, with flows between reclamation blocks ranging from 0.8–1.2 m/s. In contrast, currents in sheltered areas weaken to about 0.2 m/s. Reclamation also intensifies erosion in areas directly exposed to open flow, while promoting sediment deposition in sheltered zones. Channel discharge decreased by 20–70% after reclamation, with the greatest reductions in the Kepiting and Bokor rivers (60–70%) and the smallest in the Wonokromo River (15–20%). These findings underscore the importance of planning reclamation projects with due regard to community livelihoods and coastal ecosystem sustainability. Recommended mitigation measures include constructing connecting canals to maintain circulation, implementing staged reclamation to allow adaptive evaluation, and restoring mangrove belts along reclamation boundaries. The study highlights the value of numerical modeling as a decision-support tool for adaptive and sustainable coastal management.